PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DEPARTEMEN INJECTION PHYLON PT PRATAMA ABADI INDUSTRI SERPONG - Adi Ismanto; Krida Puji Rahayu (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
. This research aims to determine the influence of the work environment and work discipline on employee performance in the phylon injection department at PT Pratama Abadi Industri Serpong. The research method used is the quantitative method. The sampling technique used is saturated sampling. The population and sample for this research consist of 90 respondents. The analysis technique used includes instrument test analysis (validity and reliability), classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), simple linear regression analysis test, multiple linear regression analysis test, correlation coefficient analysis test, coefficient of determination analysis test, and hypothesis test. (uji t dan uji F). The research results for the Work Environment variable (X1) indicate a positive and significant partial effect on employee performance in the Injection Department of Phylon PT Pratama Abadi Industri Serpong. The t-test results (partial test) show that t count > t table (4.922 > 1.987) and significant < 0.05, namely (0.000 < 0.005). The Work Discipline variable (X2) also shows a positive and significant partial effect on employee performance in the Injection Department of Phylon PT Pratama Abadi Industri Serpong. The t-test results (partial test) show that t count > t table (9.521 > 1.987) and significant < 0.05, namely (0.000 < 0.005). The simultaneous research results indicate a positive and significant effect of the Work Environment and Work Discipline variables on Employee Performance in the Injection Department of Phylon PT Pratama Abadi Industri Serpong. The F-test results (simultaneous test) show that F count > F table (47.445 > 3.10) and significant < 0.05, namely (0.000 < 0.005). The results of the coefficient of determination test yielded an R-square value of 0.522. It can be concluded that the variables Work Environment (X1) and Work Discipline (X2) have an influence on the variable Employee Performance (Y) by 52.2%, while the remaining 47.8% is influenced by other.